2022
DOI: 10.3390/foods11172589
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated Zein Composite Nanoparticles for Efficient Delivery of Betulinic Acid: Fabrication, Characterization, and In Vitro Release Properties

Abstract: Betulinic acid (BA) has anti-inflammatory, antioxidative stress, and antitumor activities, but BA bioavailability is low due to its poor water solubility and short half-life. This study aimed to construct a BA delivery system to improve its utilization in vitro. Glycosylated zein (G-zein) was prepared using the wet heating method, and BA-loaded zein composite nanoparticles were prepared using the antisolvent method. Compared to zein, G-zein had the advantages of higher solubility and lower surface hydrophobici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The nanocomplexes were diluted to a 20 μg/ mL concentration with deionized water, and then dripped on 230-mesh copper grids. After drying naturally, the samples were imagined by TEM (JEM-1230, JEOL, Tokyo, Japan) at 80 kV to assess the microstructure of the 7S-Cur and 7S-150-Cur nanocomplexes [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The nanocomplexes were diluted to a 20 μg/ mL concentration with deionized water, and then dripped on 230-mesh copper grids. After drying naturally, the samples were imagined by TEM (JEM-1230, JEOL, Tokyo, Japan) at 80 kV to assess the microstructure of the 7S-Cur and 7S-150-Cur nanocomplexes [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was also demonstrated that BA NPs may inhibit glioma cell proliferation and that the therapeutic effect of BA NPs is influenced by the presence of CB1/CB2 receptors on the surface of glioblastoma cells [72]. BA was also encapsulated in glycosylated zein (GZ) NPs (BA-GZ NPs) [70]. Zein is a natural, biocompatible, and biodegradable polymer widely used in the pharmaceutical, biomedical, and packaging fields because of its low water vapor permeability, antibacterial activity, and hydrophobicity [103].…”
Section: Polymeric Npsmentioning
confidence: 99%
“…BA was also encapsulated in glycosylated zein (GZ) NPs (BA-GZ NPs) [ 70 ]. Zein is a natural, biocompatible, and biodegradable polymer widely used in the pharmaceutical, biomedical, and packaging fields because of its low water vapor permeability, antibacterial activity, and hydrophobicity [ 103 ].…”
Section: Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation